Gaung Masa Lalu dalam Novel Rifa’at Sang Penebus Karya Najib Mahfuz - Sufi Ikrima Sa’adah (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2021)
Modern Arabic literature owns its development to the works of Naguib Mahfouz during the five decades of his writing career. Mahfouz brings together various ancient Egyptian tales and prophetic stories into 1950s Egypt. The story that Mahfouz builds in his novels echoes the author's childhood story as well as various other stories. This article aims to explore to what extends the novel echoes the prophetic stories as well as the author’s childhood experiences. The researcher employs intextuality to meet the objective of this study. The findings reveal that Mahfouz adopt and paraphrase various events and figures from Al-Quran and the Bible then put those events and figures into a new context in Awl?d H?ratina Indonesian Edition #3 (Rifa’at Sang Penebus). Besides, Mahfouz portrays the novel’s setting as the reflection of his childhood residence.